A uranium(VI) complex with a tetradentate N1, N4-disalicyliden-S-ethylisothiosemicarbazone ligand. (28th May 2017) - Akbari, Alireza; Fasihizad, Ahad; Ahmadi, Mehdi; Machura, Barbara
Graphical abstract: A uranium complex of a tetradentate isothisemicarbazone ligand is synthesized. Structure analysis, spectral, TG and DFT studies are performed. The uranium(VI) ion adopts a pentagonal bipyramidal geometry. Abstract: The Schiff base ligand of bis-(2-hydroxybenzaldehyde)- S -ethylisothiosemicarbazone and its U(VI) complex have been prepared. Their structures were fully characterized by elemental analysis, FT-IR, molar conductivity, UV–Vis and 1 H NMR methods. X-ray diffraction has been used to determine the molecular structure of the uranium complex. The Schiff base complex was found to be pentagonal bipyramidal. The N2 O2 donor ligand was coordinated to the metal center as a tetradentate binegative agent. Computational studies were performed using the DFT method to estimate the structural preferences in tridentate and tetradentate isothiosemicarbazones. Geometry optimization and natural bond orbital analyses of the UO2 (II) complex have been further discussed in detail. The thermal stabilities of the ligand and its uranium complex have also been determined by thermogravimetric analysis (TGA).